KEPEMIMPINAN TRANSFORMASIONAL DALAM TATA KELOLA PEMERINTAHAN DAN INOVASI SEKTOR PUBLIK: KAJIAN LITERATUR: Studi Kasus: Dinas Koperasi dan UKM Provinsi Kepulauan Riau - Amelia Amelia; Arinda Amalia Putri (Jurnal Publikasi Teknik Informatika, 2025)
The submission of the Certificate of Feasibility and Propriety (SK UKK) for cooperatives in the Riau Islands Province is still carried out manually, which hinders administrative processes, especially for cooperatives located far from the Office of Cooperatives and SMEs of the Riau Islands Province. To address this issue, this internship project aims to design and develop the Feasibility and Propriety Test Application (ALPUKAT), a web-based platform that facilitates online SK UKK submissions. The system was developed using the Laravel 12 framework, the PHP programming language, and MySQL database. The application provides account registration and document upload features for cooperatives, while the Cooperative Office, acting as the administrator, can verify documents, schedule interviews, and upload meeting minutes and SK UKK certificates. The result of this internship is a functional application that can be utilized by both cooperatives and the Cooperative Office within the Riau Islands Province. The implementation of this system is expected to make the SK UKK submission process more efficient, transparent, accurate, and centralized, while also supporting the government’s efforts to promote the digitalization of public services.